2014 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2014
DOI: 10.1109/icassp.2014.6854626
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian-Cauchy mixture modeling for robust signal-dependent noise estimation

Abstract: We introduce an adaptive Gaussian-Cauchy mixture modeling for the likelihood of pairwise mean/standard-deviation scatter points found when estimating signal-dependent noise. The maximization of the likelihood is used to identify the noise-model parameters, following an adaptive mixture parameter that controls the balance between the Gaussian and the heavy-tailed Cauchy. This renders the estimation robust with respect to outliers, typically present in large quantities among the scatter points from images domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 10 publications
(23 reference statements)
0
35
0
1
Order By: Relevance
“…Likewise, the simplest LS fitting method is not robust to outliers in the scatterplot. Therefore, the use of a better variance estimator and a better (e.g., robust) fitting algorithm [19] could further improve the estimation, so to possibly deal with highly textured images such as the example in Figure 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the simplest LS fitting method is not robust to outliers in the scatterplot. Therefore, the use of a better variance estimator and a better (e.g., robust) fitting algorithm [19] could further improve the estimation, so to possibly deal with highly textured images such as the example in Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the impact of the block size, we repeat the 4 A robust variant of [1] was recently published [19] while the present article was already in press. The variant models the scatterplot points as an adaptive mixture of Gaussian and Cauchy distributions, and thus yields more accurate results in cases with outliers such as that illustrated in Figure 7.…”
Section: Experiments On Camera Raw Imagesmentioning
confidence: 99%
“…Hashemi et al [16] studied behavior of the Bayesian estimator for noisy GGD data, and showed that this estimator can be well estimated with a simple shrinkage function. Azzari et al [17] introduced an adaptive Gaussian-Cauchy mixture modeling for the likelihood of pairwise mean/standard deviation scatter points found when estimating signal-dependent noise. The maximization of the likelihood is used to identify the noise model parameters, following an adaptive mixture parameter that controls the balance between the Gaussian and the heavy-tailed Cauchy.…”
Section: Related Workmentioning
confidence: 99%
“…Although seemingly very different, they all share the same property: to keep the meaningful edges and remove less meaningful ones. The existing image denoising work can be roughly divided into Nonlocal Methods [3][4][5], Random Fields [6][7][8], Bilateral Filtering [9][10][11], Anisotropic Diffusion [12,13], and Statistical Model [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In addition, many authors have developed image denoising algorithms based on support vector machine (SVM) classification [14].…”
Section: Introductionmentioning
confidence: 99%
“…For some textured reference image, its results are even totally wrong. It should be noted that a robust version of their algorithm has been recently proposed [4]. On the other hand, the proposed algorithm gives quite reliable estimations of g (the actual value is within the estimated confidence interval, which is quite small).…”
Section: Synthetic Datamentioning
confidence: 99%